A Comparison of the Effects of “Computerized Cognitive Rehabilitation Game of Attention and Memory” and “Practical Games of Attention” on Sustained Attention, Response Inhibition, Reading Speed, and Accuracy of Reading in Students with Specific Learning Disability of Dyslexia - Mohammad Drikvand; Manijeh Shehniyailagh; Alireza Hajiyakhchali (مطالعات روانشناسی تربیتی, 2022)
The present study aimed to compare the effects of “computerized cognitive rehabilitation game of attention and memory (ARAM)” and “practical games of attention” on sustained attention, response inhibition, reading speed, and accuracy of reading in students with a specific learning disability of dyslexia. This was a field experiment with an extensive control group design, which included two test groups and a control group. The statistical population included second to fifth-grade elementary students of Andimeshk, Iran in 2021-2022. In total, 60 subjects were selected by purposive sampling and were randomly divided into three groups of 20 (two test groups and one active control group). The students were tested by having them complete the Continuous Performance Test, the Go/No-go test, and the Reading and Dyslexia Test (Nema) in the pretest and posttest stages. Data analysis was performed using multivariate analysis of covariance and the Bonferroni test. According to the results, both games had significant effects on the cognitive and reading skills of dyslexic students (P<0.001). In addition, the Bonferroni test results were indicative of the higher effectiveness of computerized cognitive rehabilitation, compared to the practical games. Conclusion: according to the results of the study, rehabilitation games (computerized and practical) could be used as an efficient method for the treatment of learning disabilities of individuals by consultants and specialists.